Thermal Damage Evaluation during Internal Cylindrical Grinding - Coto, Mario Pérez (My University, 2018)
Grinding is a widely used finishing process to attain tight tolerances and surface integrity. However, it produces high local temperatures that can alter the properties of the material, altering the microstructure of the component. As grinding is done in an already hardened material, these changes caused by overtempering or rehardening will affect the final properties of the component, reducing the lifetime of the bearing. Several analytical models used to predict this behaviour already exist but are mostly based on simple geometries. To expand the knowledge to more complex geometries, grinding experiments using similar conditions as production were performed. However, those conditions limited the ways the temperature could be directly evaluated, requiring indirect methods to obtain it, in this case the hardness profile. Three different analytical models for the decomposition of the tempered martensite were assessed, to obtain a relationship between the hardness profile and the apparent temperature. Moreover, two FE models, one focusing on the macro geometries of the workpiece and wheel and a micromodel focusing on the grinding area, were built to simulate the behaviour seen in the analytical models and the obtained results. A good fit between one of the analytical models and the hardness profile was obtained. This analytical model was derived from Malkin’s studies of the phase transformations during grinding, with consideration of the tempering effect of several consecutive grinding passes. As only the outmost layers of the component were removed during grinding while the affected area was substantially bigger, the effect of several passes had a considerable importance in the hardness drop in the outmost layers of the material. Both FE models obtained temperatures similar to those expected using analytical methods, with the macromodel having some flaws that could be attributed to the difficulties of modelling a sufficiently small mesh.
Keywords: Produktion; Materialteknik; Production; Materials Engineering